DIGITAL STORYTELLING THROUGH VLOG AS A REBRANDING MEDIA FOR BASUKI TJAHAJA PURNAMA - Alan Dermawan (Mediakom, 2020)
After being released from prison for the blasphemy case, politician Basuki Tjahaja Purnama has returned to politics and rebuilding his reputation. Using vlog as a medium, Basuki presents a new personality as “BTP” which had more positive attitude than his past self as “Ahok”. This study aims to identify digital storytelling in Basuki's vlog as a form of rebranding activities he undertakes. The research was conducted through critical paradigm with semiotics analysis by Fiske. Data collected from a vlog on “Panggil Saya BTP” Youtube channel. The results showed that Basuki consistently displayed rebranding activities through storytelling in vlogs. The rebranding activity was applied by Basukithrough new name, new logo, and new slogan, which was carried out to replace the negative image of his past. Although there was a lack of technical storyplotting elements, the construction of positive impressions were consistently portrayed by Basuki in his vlog through storytelling, both explicitly through content and implicitly through gestures. The presence of Basuki on Youtube could be an example of the successful adoption of new media in political communication conducted by politicians after experiencing a reputation crisis.